Optimization of Sharia Fintech in the Development of Green Bonds and Sustainable Investments - Judijanto, Loso; Ermaini, Ermaini; Kaswoto, Junet; Arumingtyas, Fida; Sudarmanto, Eko (West Science Islamic Studies, 2025)
This study examines the optimization of Sharia fintech in the development of green bonds and sustainable investments in Indonesia, using a qualitative analysis based on interviews with five key informants from various sectors, including fintech, finance, and regulatory bodies. The findings highlight the significant role of Sharia fintech in promoting sustainable investments, especially in the context of green bonds, by democratizing access to investment opportunities and aligning financial products with ethical, Sharia-compliant principles. However, challenges such as unclear regulatory guidelines and the need for technical expertise in ensuring Sharia compliance were identified. The study also underscores the potential for synergy between Sharia finance and sustainable investment goals, with recommendations including the creation of standardized regulatory frameworks, the promotion of financial literacy, and the use of advanced technologies like blockchain to enhance transparency. The results suggest that while the integration of Sharia fintech with green bonds holds great promise, further collaboration among stakeholders and a clear regulatory approach are essential for its successful implementation.